Et tu Mucor? - Khatri, Anadi; Prasai, Gunjan; Pandey, Mukesh; Kharel, Muna; Bohara, Dikshya; Panthi, Madhav; Thapa, Najara; Jha, Bhaskar; Pradhan, Eli (Nepalese Journal of Ophthalmology, 2021)
Introduction: Recently, the Indian subcontinent has been hard hit by the second wave of COVID-19. Along with it, the region has become a hot spot for mucormycosis infection in patients with COVID-19. The aim of this paper is to provide a scientific overview on the status of mucormycosis in pre-COVID-19 era and on how COVID-19 could have directly or indirectly expose the hidden burden of mucormycosis globally. Materials and methods: This paper is structured as a narrative review and is based on relevant published literature on both COVID-19 and mucormycosis. Conclusion: Mucormycosis in the pre-COVID-19 era was almost a neglected entity. It was because the risk factors for both - More severe COVID-19 infections and Mucormycosis are almost similar – COVID-19 might have helped to expose the true magnitude of the mucormycosis and flagging it as a major public health concern requiring a revisit by medical science.